Analysis Of Students’ Mathematical Problem-Solving Ability Based On Judging and Perceiving Personality Types - Zella Eminarti; Eline Yanty Putri Nasution (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
Problem-solving ability is one of the essential skills in mathematics education at the university level. However, there has been limited research specifically examining the influence of personality types on this ability, especially in the context of Systems of Linear Equations in Three Variables (SPLTV). This study aims to analyze the mathematical problem-solving ability of students based on Judging and Perceiving personality types. The research approach used is qualitative with a case study design. The subjects of the study consist of four students from the Tadris Mathematics program at IAIN Kerinci, selected based on the results of the MBTI test, consisting of two students with the Judging personality type and two with the Perceiving personality type. The research instruments include an SPLTV test and an interview guide, while data analysis techniques are carried out through data reduction, data presentation, and drawing conclusions using the Miles and Huberman model. The results show that students with the Judging personality type tend to excel in planning and executing problem-solving strategies systematically but are less strong in evaluating results. Conversely, Perceiving students demonstrate flexibility in understanding problems and devising strategies but tend to lack in evaluative aspects and structured presentation. These findings emphasize that personality types play a role in shaping students' problem-solving patterns, suggesting the need for teaching strategies that consider the personality characteristics of each individual.